Peran Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kinerja Guru; Sebuah Systematic Literature Review - Nurmini Fitri (Journal of Innovation in Teaching and Instructional Media, 2025)
Employing a Systematic Literature Review (SLR) methodology, this study aims to investigate the influence of school principal leadership on enhancing teacher performance. Creating a setting that encourages learning and so improves general educational quality depends much on school leadership. This study finds several leadership styles including transformative, cooperative, and empowerment-based ones that affect teacher performance. According to the study’s findings, effective principals can raise teacher performance by giving ongoing professional help, promoting honest and clear communication, and building an inviting and inclusive work environment. These elements can greatly increase teachers’ motivation, dedication, and job happiness, which directly affects the quality of their instruction. Furthermore, highlighted as a major aspect in supporting enhanced teacher performance is the development of teacher capacity through instruction and the provision of good criticism. According to the study, the ongoing enhancement of teachers’ performance depends on adaptive, forward-thinking, and empowering leadership by school heads acting as a critical catalyst. School leaders therefore have to constantly create leadership that aids teachers’ professional development.